2016
DOI: 10.1089/ten.tec.2016.0053
|View full text |Cite
|
Sign up to set email alerts
|

A Flow Perfusion Bioreactor System for Vocal Fold Tissue Engineering Applications

Abstract: The human vocal folds (VFs) undergo complex biomechanical stimulation during phonation. The aim of the present study was to develop and validate a phono-mimetic VF flow perfusion bioreactor, which mimics the mechanical microenvironment of the human VFs in vitro. The bioreactor uses airflow-induced self-oscillations, which have been shown to produce mechanical loading and contact forces that are representative of human phonation. The bioreactor consisted of two synthetic VF replicas within a silicone body. A ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Alginate-based scaffolds, however, were shown to offer poorly regulated degradation due to the absence of enzymes in mammals to break down alginate 82 . The use of polyethylene glycol tetra acrylate as the cross-linking agent for a composite injectable hydrogel composed of thiolated-HA and thiolated-Ge was investigated to overcome the fast degradation rate and to enhance the mechanical and biochemical stability of the scaffolds 2 . Although no cytotoxicity was observed in vitro , and the encapsulated cells synthetized Col-I and Col-III after 7 days in culture, our recent in vivo study in rabbits showed serious inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alginate-based scaffolds, however, were shown to offer poorly regulated degradation due to the absence of enzymes in mammals to break down alginate 82 . The use of polyethylene glycol tetra acrylate as the cross-linking agent for a composite injectable hydrogel composed of thiolated-HA and thiolated-Ge was investigated to overcome the fast degradation rate and to enhance the mechanical and biochemical stability of the scaffolds 2 . Although no cytotoxicity was observed in vitro , and the encapsulated cells synthetized Col-I and Col-III after 7 days in culture, our recent in vivo study in rabbits showed serious inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid hydrogels had a half-life of more than 35 days and they featured a greater biochemical stability than that of the HA-based hydrogels previously used for STE with half-life of 2–3 weeks in cartilage, 3–5 days in vocal fold, less than one day in epidermis, and a few minutes in blood 2 , 85 . The hydrogels with higher GCS concentration (G1s) were more resistant to enzymatic degradation over the first 30 days than those with lower GCS concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations